Consumer-run services research and implications for mental health care - Segal, S. P. (Epidemiol Psychiatr Sci, 2016)
Mental health consumers/survivors developed consumer-run services (CRSs) as alternatives to disempowering professionally run services that limited participant self-determination. The objective of the CRS is to promote recovery outcomes, not to cure or prevent mental illness. Recovery outcomes pave the way to a satisfying life as defined by the individual consumer despite repetitive episodes of disorder. Recovery is a way of life, which through empowerment, hope, self-efficacy, minimisation of self-stigma, and improved social integration, may offer a path to functional improvement that may lead to a better way to manage distress and minimise the impact of illness episodes. ‘Nothing about us without us’ is the defining objective of the process activity that defines self-help. It is the giving of agency to participants. Without such process there is a real question as to whether an organisation is a legitimate CRS or simply a non-governmental organisation run by a person who claims lived experience. In considering the effectiveness of CRSs, fidelity should be defined by the extent to which the organisation's process conveys agency. Unidirectional helping often does for people what they can do for themselves, stealing agency. The consequence of the lack of fidelity in CRSs to the origins of the self-help movement has been a general finding in multisite studies of no or little difference in outcomes attributable to the consumer service. This, from the perspective of the research summarised herein, results in the mixing of programmatic efforts, some of which enhance outcomes as they are true mutual assistance programmes and some of which degrade outcomes as they are unidirectional, hierarchical, staff-directed helping efforts making false claims to providing agency. The later CRS interventions may provoke disappointment and additional failure. The indiscriminate combining of studies produces the average: no effect.